Micro Business Module on pig farming in Bay Islands - KUNDU, M S; KUNDU, A; Jeyakumar, S (Indian Farming, 2015)
The Central Agricultural Research Institute, Port Blair imparted the training programme under a new initiative called Micro Business Module (MBM) on pig farming. In this training programme different facets of pig rearing like feeding, care and management of pigs were imparted. After getting the training Mr. Sekhar is running a piggery farm successfully and converted its pig farm into composite livestock cum horticulture unit. His monthly income from pig farm is about Rs three thousand five hundred.